Penerapan Model Pembelajaran Inkuiri Berbantuan Media Konkret Untuk Meningkatkan Hasil Belajar Muatan Pelajaran Matematika - Sefnita Eka Sutarti, N. P.; Citra Wibawa, I M (Universitas Pendidikan Ganesha, 2018)
This study aims to know the improvement of mathematics learning outcomes by applying the concrete media-based inquiry learning model in the third grade students of SD N 4 Kaliuntu in the academic year 2017/2018. This type of research was Classroom Action Research (PTK) which was implemented in two cycles. The subjects of this study were 39 students in the third grade of SD N 4 Kaliuntu in the academic year of 2017/2018. The objects of this research were the concrete media-based inquiry learning model and the learning result of Mathematics. The data in this study were collected by the test method. Data were analyzed by quantitative and qualitative analysis method. The results showed that there was an increase on the students' mathematics learning outcomes. Based on the observation result, the average value of teacher activity was 23 with good category and the average score of student activity was 51 with enough category in cycle I and there was improvement in cycle II with the average of teacher activity iof 27,5 with very category good and average student activity score of 78,5 with very good category. In addition, based on data analysis, the average percentage of students' learning achievement in cycle I was 66,67% (medium category), increasing to 85% (high category) in cycle II. Based on the results of this study, it can be concluded that the implementation of inquiry learning model in concrete media can improve the learning outcomes of Mathematics students of third grade in SD N 4 Kaliuntu in the academic year of 2017/2018.